IMPLEMENTASI PENDIDIKAN BERBASIS ADAB DALAM PENGEMBANGAN KARAKTER : DOI: https://doi.org/10.37850/cendekia.v12i1.88 - Khubni Maghfirotun; Eka Nur Mahzumah (Cendekia, 2020)
The morality / character of the nation's students has collapsed. This is marked by the rise of bullying, child anarchism, mass contests, free sex and so on. Seeing the importance of the role of etiquette in human life, the education world should think more seriously about the concept of planting etiquette in its students, so that the introduction and cultivation of etiquette must begin at an early age. Rasulullah SAW has taught that the example is the main factor of success in educating children. Exemplary is also the best method in children's education, especially in the early childhood period. On this basis the research formulated the formulation of the problem namely (1) How is the concept of Adab in SDI Ar-Roudloh Miru? (2) How is the Implementation of Adab Based Education in SDI Ar-Roudloh Miru-Sekaran-Lamongan? This study uses qualitative research and case studies as its research design. Research subjects in this study were students at SDI Ar-Roudloh. Data collection techniques used were observation, semistructural interviews and documentation. Data were analyzed using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The data checking technique uses triangulation techniques. The results of this study include: (1) the formation of students' character at SDI Ar Roudloh is with the Applicative Religious concept. This is evidenced by the existence of Boarding School since students go up to fourth grade. This is expected to be more intensive in applying civilized values ​​that are prioritized by the institution. The etiquette values ​​emphasized and prioritized at SDI Ar Roudloh in this case are divided into three aspects namely; Judging from the pattern of attitudes and behavior to God, patterns of behavior to fellow human beings, patterns of behavior to nature. (2) in implementing civilized education for the formation of students' character by applying the religious concept with the details of the sub-chapters above, there are several stages in order to obtain maximum results, before implementing and informing the values ​​of civilized education to students. In this case the researcher classifies into three stages; first; Socialization, second; Implementation and third; Evaluation.